Dedifferentiated liposarcoma with heterologous spindle cell rhabdomyoblastic de-differentiation: An unusual pattern expanding the morphological spectrum - Bharat Rekhi; Akshay D Baheti; Shraddha Patkar (Wolters Kluwer Medknow Publications, 2020)
Dedifferentiated liposarcoma (DDLS) is characterized by a wide histopathological spectrum. Spindle cell type of rhabdomyoblastic dedifferentiation has been rarely described in case of DDLS. A 39-year-old male presented with a recurrent retroperitoneal tumor mass, diagnosed as well-differentiated liposarcoma, for which he underwent surgical excisions on two occasions, followed by adjuvant radiation therapy previously. Computed tomogram scan his of abdomen revealed a large-sized, fat-containing recurrent, retroperitoneal mass, measuring 18.1 cm in the largest dimension. Histopathologic examination of the resected tumor revealed distinct areas of well- and dedifferentiated liposarcoma, including areas reminiscent of a myxofibrosarcoma, further progressing into a high-grade spindle cell sarcoma with fascicular and "Herringbone-like" growth patterns (fibrosarcoma-like). Immunohistochemically, high-grade spindle cell sarcomatous (dedifferentiated) component displayed distinct positivity for desmin and MyoD1, along with focal tumor nuclei, showing nuclear positivity for myogenin. Both well-differentiated liposarcomatous and dedifferentiated components displayed diffuse, intense nuclear positivity for MDM2 (overexpression) and p16INK4A. Furthermore, upon testing tumor sections displaying spindly sarcomatous areas for MDM2 amplification, by FISH technique, nearly all tumor cells displayed MDM2 gene amplification. This case constitutes one of the rare cases of DDLS displaying spindle cell rhabdomyoblastic dedifferentiation. Its diagnostic and treatment implications are discussed herewith.